Tumor-on-chip platforms for breast cancer continuum concept modeling - Neagu, Anca-Narcisa; Whitham, Danielle; Bruno, Pathea; Versaci, Nicholas; Biggers, Peter; Darie, Costel C. (Frontiers in Bioengineering and Biotechnology, 2024)
Our previous article entitled "Proteomics and its applications in breast cancer", proposed a Breast Cancer Continuum Concept (BCCC), including a Breast Cancer Cell Continuum Concept as well as a , which reflects the continous flow of the metastatic cascade at cellular level, integrating multiple populations of BC cells and tumor-associated cells which progress from the primary tumor site toward distant organotropic organs. This multicellular flow is acompagnied by the Breast Cancer Proteomic Continuum Concept. , whereas each phenotype of both neoplastic and tumorassociated cells, within primary tumor microenvironment towards distant secondary tumoral niches, is characterized by an addaptive proteomic profile detected by mass spectrometry (MS)-based approaches in solid or liquid biopsies. Breast cancer-on-chip (BCoC), breast cancer liquid biopsy-on-chip (BCLBoC), and breast cancer metastasis-on-chip (BCMoC) models successfully recapitulate and reproduce in vitro the principal mechanisms and events involved in BCCC. Thus, BCoC, BCLBoC, and BCMoC platforms allow for multiple cell lines co-cultivation, to reproduce BC hallmark features, recapitulating cell proliferation, cell-to-cell communication, BC cell-stromal crosstalk and stromal activation, effects of local microenvironmental conditions on BC progression, invasion/epithelial-mesenchymal transition (EMT)/migration, intravasation, dissemination through blood and lymphatic circulation, extravasation, distant tissues colonization, and immune escape of cancer cells. Moreover, tumor-on-chip platforms are used for studying the efficacy and toxicity of chemotherapeutic drugs/nano-drugs or nutraceuticals. Therefore, the aim of this review is to summarize and analyse the main bio-medical roles of on-chip platforms that can be used as powerful tools to study the metastatic cascade in BC. As future direction, integration of tumor-on-chip platforms and proteomics-based specific approaches can offer important cues about molecular profile of the metastatic cascade, alowing for novel biomarker discovery, especially based on non-invasive liquid biopsies. Novel microfluidics-based platforms integrating specific proteomic landscape of human milk, urine, and saliva could be useful for early and noninvasive BC detection. Also, risk-on-chip models may improve BC risk assessment and prevention based on the identification of biomarkers of risk. Moreover, multi-organ-on-chip systems integrating patient-derived BC cells and patient-derived scaffolds have a great potential to study BC at integrative level, due to the systemic nature of BC, for personalized and precision medicine. We also